Being fun: An overlooked indicator of childhood social status. Issue 5 (19th March 2020) - Laursen, Brett; Altman, Robert L.; Bukowski, William M.; Wei, Li
Abstract: Objective: The present study concerns an overlooked trait indicator of childhood peer status: Being fun . The study is designed to identify the degree to which being fun is uniquely associated with the peer status variables of likeability and popularity. Method: Two studies of children in grades 4 to 6 (ages 9 to 12) are reported. The first involved 306 girls and 305 boys attending school in northern Colombia. The second involved 363 girls and 299 boys attending school in southern Florida. Students completed similar peer nomination inventories, once in the first study and twice (8 weeks apart) in the second. Results: In both studies, being fun was positively correlated with likeability and popularity. In the second study, being fun predicted subsequent changes in likeability and popularity, after controlling for factors known to be related to each. Initial likeability and popularity also predicted subsequent changes in perceptions of being fun. Conclusions: Anecdotal evidence suggests that children are intensely focused on having fun. The findings indicate that this focus extends beyond the immediate rewards that fun experiences provide; some portion of peer status is uniquely derived from the perception that one is fun to be around.